The Influence Of Corporate Social Responsibility (CSR) On Financial Performance: A Comparative Study In Several Countries - Ninda Maya Firnanda; Maidatus Zahroh; Hwihanus Hwihanus (Jurnal Riset Akuntansi, 2024)
The impact of corporate social responsibility (CSR) on financial performance across many nations is examined in this research. This study aims to examine the findings of studies conducted in different nations and sectors about the impact of CSR on CFP. This study's methodology, meta-analysis, makes use of secondary data from worldwide publications published in a number of nations, including southern Africa, Nigeria, Italy, Pakistan, and Jordan. The findings demonstrated that CSR does not always provide reliable outcomes. According to the study's findings, corporate social responsibility (CSR) may improve an organization's financial success, but how effective it is will vary greatly depending on the unique socioeconomic and regulatory circumstances of each nation and sector.